On the spectra of some g-circulant matrices and applications to nonnegative inverse eigenvalue problem - Andrade, Enide (2020)
A $g$-circulant matrix $A$, is defined as a matrix of order $n$ where the elements of each row of $A$ are identical to those of the previous row, but are moved $g$ positions to the right and wrapped around. Using number theory, certain spectra of $g$-circulant real matrices are given explicitly. The obtained results are applied to Nonnegative Inverse Eigenvalue Problem to construct nonnegative, $g$-circulant matrices with given appropriated spectrum. Additionally, some $g$-circulant marices are reconstructed from its main diagonal entries.